FACTORS INFLUENCING TOMATO MARKETING IN ILE-IFE, OSUN STATE, NIGERIA - Ojedokun, Olajide (Journal on Processing and Energy in Agriculture, 2020)
This study was conducted to identify the factors influencing tomato marketing in Ile-Ife, Osun State, Nigeria. Primary data were collected from a total of 100 tomato marketers using a multistage sampling technique. The data were analysed using descriptive statistics, gross margin analysis and multiple regression analysis. The result obtained revealed that wholesalers had a higher gross margin than retailers. Gender, education level and transportation costs were found to influence the marketing margin of retailers, whereas household size and transportation costs influenced the marketing margin of wholesalers. The study therefore recommends that tomato marketers should be encouraged into wholesale marketing. This can be achieved by subsidization and the implementation of an efficient marketing system.
Keywords: tomato, retailer, wholesaler, gross margin, determinants, the Ile-Ife region